Application of problem-based learning combined with responsibility-based teaching model in the clinical teaching of nursing students (PBL教学法结合责任制教学在实习护生带教中的应用研究) - REN Huijuan (任慧娟); YUAN Xuemei (袁雪梅); QU Yue (曲悦) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of problem-based learning(PBL)combined with responsibility-based teaching model in the clinical teaching of nursing students. Methods A total of 50 nursing students who participated in the internship between July 2020 and April 2021 were recruited as the control group, and routine teaching method was adopted during their clinical internship. Another 50 nursing students who participated in the internship between July 2021 and April 2022 were recruited as the observation group, and the PBL combined with responsibility-based teaching model were used in the clinical teaching. The practical skills, theoretical knowledge assessment outcomes, general performance, attendance and score of the Self-regulated Learning Scale in Clinical Nursing Practice for nursing students (SRLS-CNP)were evaluated and compared between two groups. Results The scores of practical skills and theoretical knowledge assessment in the observation group were higher than those in the control group(P＜0. 01). The outcomes of general performance and attendance assessment in the observation group were higher than those in the control group(P＜0. 01). The score of SRLS-CNP was increased in both groups after intervention, and score of SRLS-CNP in the observation group was higher than that in the control group after internship(P＜0. 01). Conclusion The combination of PBL teaching and responsibility-based teaching can improve the comprehensive nursing ability of the nursing students during the internship. (目的 探讨以问题为基础的学习(PBL)的教学法结合责任制教学模式在实习护生带教中的应用效果, 为临床护理带教工作提供参考。方法 选取2020年7月-2021年4月在科室实习的护生50例为对照组, 采取传统带教模式; 选取2021年7月-2022年4月在科室实习的护生50例为观察组, 实施PBL教学法和责任制教学相结合模式下的带教。对比两组理论与操作考核成绩、综合表现和出勤情况, 采用护生临床护理实践自我调节学习量表(SRLS-CNP)评价护生自我调节学习能力。结果 观察组理论考试与操作考试成绩均高于对照组, 差异有统计学意义(P＜0. 01)。观察组综合表现成绩和出勤情况评分均高于对照组, 差异有统计学意义(P＜0. 01)。实习后, 两组护生SRLS-CNP量表评分均较实习前提高, 且观察组SRLS-CNP评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 运用PBL教学法结合责任制教学开展临床带教, 能够有效提高实习护生实习期间的综合护理能力。)